A Geographical Information System-based Mapping Model for Aligning Vocational High Schools with Industrial Needs - A. Ana; Dwiyanti, Vina; Sari, Ana Ramdani; Saripudin, S.; M. Muktiarni (Journal of Technical Education and Training, 2025)
Vocational High Schools (SMKs) are essential in linking education with regional industry needs. However, mismatches between SMK programs and industry demands often hinder graduate employability. This study develops a GIS-based mapping model to analyze the spatial alignment between SMKs and industries in Greater Bandung, covering Bandung City, West Bandung, Bandung Regency, and Cimahi City. A descriptive quantitative method was used, employing ArcGIS 10.2 and satellite imagery. Data included 39 public SMKs and 2,535 industries, categorized by vocational sectors based on Ministry Regulation No. 024/H/KR/2022. Mapping and spatial overlay analysis were conducted to assess alignment. Findings show limited and uneven alignment. While some SMKs align with the manufacturing sector, key sectors such as tourism, health, and creative economy lack nearby or relevant SMK support. Many schools are not strategically located near related industries, reducing collaboration and practical training opportunities. The study recommends integrated spatial planning that aligns vocational education with local economic strengths. Improved coordination between education and industry stakeholders is essential to enhance relevance and job outcomes for graduates.